Agility and flexibility: what's the difference? - Baker, John (Cranfield University, 1996)
There is growing interest in the concept of “agile organisations” amongst management practitioners and academics. Early publications have been largely practitioner-oriented and have been at pains to claim that this is a new idea, with fundamental differences to other concepts such as flexibility and lean production. However, there has been little direct explanation of what these differences actually are. A particular area of confusion appears to be over the difference between “agility” and the established concept of “flexibility”, a confusion which this paper starts to attempt resolving.